2008
DOI: 10.1016/j.jacc.2007.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cardiac Allografts With Mild and Moderate Left Ventricular Hypertrophy Can Be Safely Used in Heart Transplantation to Expand the Donor Pool

Abstract: Short- and long-term survival rates and rates of LVH at follow-up were similar in both groups, suggesting that donor hearts with mild and moderate LVH can be safely used in HTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 20 publications
0
29
0
12
Order By: Relevance
“…Among 427 cases, 62 had interventricular septum thickness >12 mm. Survival in patients with or without left ventricular septum thickness >12 mm was similar [3]. The presence of donor coronary artery lesions has always been considered exclusion criteria.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Among 427 cases, 62 had interventricular septum thickness >12 mm. Survival in patients with or without left ventricular septum thickness >12 mm was similar [3]. The presence of donor coronary artery lesions has always been considered exclusion criteria.…”
Section: Discussionmentioning
confidence: 89%
“…Mild-to-moderate left ventricular hypertrophy may also not be considered an exclusion criteria any more. Since short-and long-term postoperative evaluations were similar in the two different recipient groups with organs from elderly donors, Goland et al indicated that mild-to-moderate left ventricular hypertrophy could be tolerated [3].…”
Section: Introductionmentioning
confidence: 99%
“…6,7,12,13 Baseline donor CAD and left ventricular hypertrophy appear to increase the risk of significant CAV (especially early after OHT). 5,14,15 Recipient risk factors for CAV include higher recipient body mass index, older age, male recipient, prior ischemic heart disease, ventricular assist device support, and recent infection. 6,7,12 Traditional atherosclerotic risk factors such as hypertension, hyperlipidemia (including triglyceride/highdensity lipoprotein ratio .3), diabetes, and smoking also increase the risk of CAV.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The presence of LV hypertrophy may also deter the use of donor hearts (73). However, recent studies demonstrated that hearts with mild to moderate left ventricular hypertrophy have similar short-and longer-term outcomes provided other risk factors are simultaneously considered (e.g., ischemic time) (74). There are few data comparing echocardiographic findings and pulmonary artery catheter measurements, but recent reports suggest that many hearts with adverse initial hemodynamics or echocardiography can be successfully managed to a state where transplantation is possible (8).…”
Section: Echocardiographic Assessment Of the Donor Heartmentioning
confidence: 99%